Distribution spatiale des génotypes dans une population de chêne vert (Quercus ilex L.), flux génique et régime de reproduction (Genetics Selection Evolution, 1988)
Spatial distribution of genotypes in holm oak (Quercus ilex L.) was analyzed within a site using three allozyme systems (PGI-I, IDH-1, ADH-1) as markers. No aggregation effect of the genotypic classes could be pointed out at any locus. Wright’s fixation index calculated over all the individuals of the site was not significantly different from zero (Fis = 0.02), indicating a situation close to the Hardy-Weinberg equilibrium expectation. Allele frequencies in the effective pollen responsible for the observed progenies of nine open-pollinated individual trees of the site were significantly different (P < 0.05) even when the parents were very close. Finally, the results clearly show that the trees are not necessarily pollinated by their neighbours, but rather by those individuals that are both synchronous phenologically and that invest primarily in the male function.